Building evidence for family group decision-making in child welfare: operationalizing the intervention. Issue 3 (27th May 2022) - Lalayants, Marina; DePanfilis, Diane; Merkel-Holguin, Lisa; Baldwin, Melinda; Schmidt, Michele; Treinen, Julie; Zuñiga, Danielle; Mackereth, Casey; Anderson, Taylor
ABSTRACT: Family group decision-making (FGDM) is a system reform strategy that positions family groups as decision-making leaders in family meetings, based on family-centered, strength-based, culturally relevant principles. Evidence of outcomes of family meetings is equivocal due to the differences in models and insufficient operationalization of core components. An important phase of intervention research mandates the importance of clearly operationalizing the intervention before efficacy or effectiveness can be evaluated. Using the framework for building evidence in child welfare, this paper reports on operationalization of core components of FGDM designed to serve three target child welfare populations.